Pengaruh Pemberian Token Ekonomi terhadap Kepatuhan Minum Obat pada Klien Skizofrenia di Ruang Kunti Rumah Sakit Jiwa Provinsi Bali - Julianti Tandilolo; Ni Komang Matalia Gandasari; Desak Putu Risna Dewi (Jurnal Keperawatan Terapan, 2020)
Treatment for schizophrenia clients requires a long period of time so that it causes saturation of taking medication and the clients level of compliance taking the drug decreases. One therapeutic technique to improve compliance behavior is to provide positive reinforcement through economic tokens. This study aims to determine the effect of economic tokens on adherence to taking medication in schizophrenic clients. This type of research is quasi experiment using One group pre post test design. The sample in this study were schizophrenic patients who were not compliant to take medication as many as 28 people using purposive sampling technique. Data collection uses observation sheets. The results showed the majority of pre test medication adherence were 67.9 percent in the low category. Compliance with taking the post test medication showed that most were 57.1 percent in the high category. Wilcoxon Sign Rank Test results obtained z count is 4.882 more than z table is 1.96 and p is 0.001, the results of this analysis indicate there is an effect of giving economic tokens on adherence to taking medication in schizophrenia patients. The study concluded that economic tokens had a significant effect on adherence to taking medication in schizophrenia patients. It is recommended to apply SPO economic token therapy, provide economic token therapy on an ongoing basis and develop further research by increasing the number of meetings in each therapy session.